Design of a web-based information system for notary service management and legal document archiving at the Alex Edwar Notary Office - Rahma Aulia; Ahmad Ferdian Shobur (Jurnal Mantik, 2026)
Administrative activities at Alex Edwar Notary Office were still performed using semi-manual procedures, causing difficulties in document tracking, service status monitoring, and legal document archiving. This study aimed to develop a web-based information system to support the management of notary services and legal document archives. The system was developed using the Waterfall method, with PHP and MySQL for implementation. The developed system integrates user authentication, client management, notary service management, service submission, document status monitoring, legal document archiving, and report generation. Black Box Testing was conducted using eight functional test scenarios, and all scenarios passed, resulting in a 100% test pass rate. The developed system provides centralized management of notary services and legal document archives and supports document status monitoring for administrators, notaries, and clients